The myths and truths of lean transformations : how to successfully make the transition from theory to effective deployment - Kelly, Raymond, 1952- (Routledge/Productivity Press, 2019)
This book is a crucial resource for Lean practitioners (experienced or not) who are seeking: insight on how to gain more from their Lean efforts, how to overcome resistance to change (that is, to effectively convey 'What’s in it for me?' to their business associates), and to understand how other companies have overcome the barriers to implementing Lean and incorporated it as the common-sense approach to continuous improvement. The author shares his specific experiences with Lean transformations—some successes and some failures. His insightful perspective shows readers how the understanding of Lean progresses from theory to common sense to common practice. The Lean initiative is not merely a transformation of skills, but the development of a robust continuous-improvement culture. The book includes more than 60 case-in-point examples, across a diversified range of industries, based on the author’s hands-on experience with many multinational corporations. These case-in-point examples show transformations that have resulted in.